Manufacturing process selection for pet bottles using analytical hierarchy process - Razali, Adibah (2013)
This thesis discusses on manufacturing process selection of PET bottles using AHP. There are six factors to be considered which are geometry of the design, production characteristics, cost consideration, material, ease of maintenance, as well as availability of equipments and labors. The main objective of this project is to select the most appropriate manufacturing process for PET bottles based on these factors. Therefore, this study emphasizes on the usage of one of multi criteria decision making (MCDM) tools namely AHP. The AHP requires data for all factors to be used in the pairwise comparisons. Data for sub factors are widely available in handbooks. However, direct interviews by distributing questionnaires to experts in the manufacturing process for PET bottles were done to get accurate data on six main factors. From the analysis using AHP, this study reveals that the extrusion blow molding is the most appropriate process for PET bottles with a priority of 28.55%. Injection molding has a priority weight of 21.84% and then followed by blow molding (19.24%), stretch blow molding (17.52%), and lastly is injection blow molding (12.82%). After that, several sets of sensitivity analyses were performed using Expert Choice software to verify whether any small changes to each of the aforementioned factors will affect the results obtained through previous AHP analyses.Further research using different MCDM tools is recommended to enhance knowledge on this area.